The Memoir Method in Educational Research From an Australian Perspective - Maniam, Vegneskumar (Qualitative Sociology Review, 2014)
This paper reviews some key memoir studies, which were carried out in South Australia, and considers their process of data collection and analysis. A second aim is to explore the current status and usefulness of Znaniecki’s memoir approach in contemporary educational research. Smolicz followed Znaniecki in emphasizing the need to accept social and cultural values and actions as facts, just as human agents themselves accept them. Every individual was seen as a member of various group social systems and interpreted as a center of experience and actions based on the cultures of those groups. Smolicz also adopted Znaniecki’s memoir method of collecting and analyzing personal data in order to understand the actions and attitudes of young people of immigrant families and their educational experiences in Australian schools. These conscious human agents played an important role in maintaining and changing their group’s cultural systems. This paper highlights examples of various forms of memoirs collected from four different studies focused specifically on the issue of cultural identity. The comments of the participants, who came from various minority ethnic groups living in Australia, illustrate the nature of the comments made, as well as the researchers’ analysis and findings. The research studies of Smolicz and his associates demonstrate that memoir method has an important place in understanding the culture of different groups, which can be applied in many contexts – global, ethnic, national, and local.